2022
DOI: 10.2147/cmar.s334521
|View full text |Cite
|
Sign up to set email alerts
|

KLF16 Downregulates the Expression of Tumor Suppressor Gene TGFBR3 to Promote Bladder Cancer Proliferation and Migration

Abstract: Krüppel-like factors (KLFs), which comprise 17 family members, exert important functions during the development of cancer. The role of KLF16 seems controversial in carcinogenesis because both tumor suppressive and promoting effects have been reported. Methods:The expression level of KLF16 was analyzed based on public data sets from The Cancer Genome Atlas (TCGA) and evaluated by immunohistochemical (IHC) staining. CCK8 assay, colony formation analysis, transwell assays and the PI/Annexin V-APC assay kit were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…TGFBR3 inhibits the development of tumors such as renal cancer, lung cancer, and liver cancer, and has been considered a tumor-inhibiting factor ( 48 - 50 ). Encouragingly, Chen et al discovered in 2022 that TGFBR3 was negatively correlated with the progression and metastasis of bladder cancer ( 51 ). The results of our study confirmed this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…TGFBR3 inhibits the development of tumors such as renal cancer, lung cancer, and liver cancer, and has been considered a tumor-inhibiting factor ( 48 - 50 ). Encouragingly, Chen et al discovered in 2022 that TGFBR3 was negatively correlated with the progression and metastasis of bladder cancer ( 51 ). The results of our study confirmed this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that LHX3 is a biomarker for predicting prognosis in patients with advanced hepatocellular carcinoma [11]. All these phenomena suggest the importance of LHX3 in regulating the development of malignant diseases.TGFBR3 acts as a co-receptor for TGF-β and undergoes lysogenic cleavage under the action of metalloproteinases, the soluble TGFBR3 produced after shedding of the extracellular functional region can competitively bind to tumor autocrine TGF-B and inhibit human tumor progression by blocking the pro-oncogenic effect of TGF-β [5]. TGFBR3 acts as a co-receptor for inhibin A but not inhibin B in mouse gonadotropin cells in vivo [17], and bioinformatic results suggest that TGFBR3 can act as an invasive pituitary tumor [28].…”
Section: Discussionmentioning
confidence: 99%
“…KLF8 is activated by TGF-β1 through SMAD2 and promotes ovarian cancer progression ( 96 ). KLF16 is an oncogene in bladder cancer due to its inhibition of TGF-β receptor 3, which inhibits tumor proliferation by a non-canonical TGF-β pathway ( 97 , 98 ). KLF17 is a crucial regulator of TGF-β signaling, which forms a positive feedback loop with SMAD3, and the expression of both is often positively correlated in cancer tissues.…”
Section: Klfs-mediated Molecular Regulationmentioning
confidence: 99%